2010
DOI: 10.1088/0026-1394/47/4/006
|View full text |Cite
|
Sign up to set email alerts
|

UV/ozone cleaning of platinum/iridium kilogram mass prototypes

Abstract: Platinum–iridium (Pt/Ir) kilogram mass prototypes are known to gain contamination from the environment in which they are stored. The current method of cleaning these mass prototypes is called nettoyage–lavage and involves the physical rubbing of a kilogram with a chamois leather cloth soaked in a solvent followed by removal of any solvent residue using a jet of steam water. The manual nature of the technique means the effectiveness of the cleaning process is reliant on the human operative. An alternative clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…A direct comparison of hydrogen plasma and UV/ozone revealed that hydrogen also reduces species of oxygen while UV/ozone results in an oxidation [11]. The latter result is in agreement with earlier findings [5] while Davidson et al found no evidence for an oxidation [8,9]. However, the various results clearly demonstrated that both modern processes lead to different but fully reproducible initial surface chemical states, and thus are most preferable for a cleaning process and for the periodic re-initialization of primary mass standards.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…A direct comparison of hydrogen plasma and UV/ozone revealed that hydrogen also reduces species of oxygen while UV/ozone results in an oxidation [11]. The latter result is in agreement with earlier findings [5] while Davidson et al found no evidence for an oxidation [8,9]. However, the various results clearly demonstrated that both modern processes lead to different but fully reproducible initial surface chemical states, and thus are most preferable for a cleaning process and for the periodic re-initialization of primary mass standards.…”
Section: Introductionsupporting
confidence: 84%
“…The same variable findings about oxidation upon UV/ozone treatment were reported for PtIr. Earlier measurements [6] found that the surface was oxidized while newer experiments [9] give no indication of an oxidation.…”
Section: Quartz Crystal Microbalancementioning
confidence: 97%
See 1 more Smart Citation
“…Both techniques have the advantage that they are noncontact so the effectiveness and repeatability of the cleaning achieved should be governed solely by the parameters set (UV intensity and ozone concentration or plasma intensity and pressure). Both METAS (Switzerland) [16,17] and NPL (UK) [18,19] have evaluated UV/ozone and H-plasma non-contact cleaning methods in parallel with the traditional nettoyage-lavage method. The results from the two laboratories are shown in Figs.…”
Section: Cleaning Of Primary Mass Standardsmentioning
confidence: 99%
“…Among the potential materials it is one of the chemically most resistant and forms no oxides under normal conditions. Physisorbed contaminations can largely be removed by various cleaning methods such as nettoyage-lavage [12], UV/ozone [13][14][15] or hydrogen plasma [16,17]. These characteristics make PtIr quite favourable as a material for mass standards of highest stability.…”
Section: Introductionmentioning
confidence: 99%